2020
DOI: 10.1053/j.ajkd.2019.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Mortality in a Multinational Cohort of Adults Receiving Hemodialysis

Abstract: Rationale & Objective: Clinical practice guidelines for dietary intake in hemodialysis focus on individual nutrients. Little is known about associations of dietary patterns with survival. We evaluated the associations of dietary patterns with cardiovascular and all-cause mortality among adults treated by hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Compared with the lowest tertile of servings per week (a median of 2), higher fruit and vegetable consumption was associated with a lower risk of death 162 . However, in the same cohort, no associations were found between adherence to a Mediterranean diet, DASH diet 163 or dietary patterns suggestive of a plant-based or Western diet 164 and risk of death. Taken together, these findings might suggest that it is the consumption of fruits and vegetables rather than the overall dietary pattern that is beneficial.…”
Section: Nature Reviews | Nephrologymentioning
confidence: 86%
“…Compared with the lowest tertile of servings per week (a median of 2), higher fruit and vegetable consumption was associated with a lower risk of death 162 . However, in the same cohort, no associations were found between adherence to a Mediterranean diet, DASH diet 163 or dietary patterns suggestive of a plant-based or Western diet 164 and risk of death. Taken together, these findings might suggest that it is the consumption of fruits and vegetables rather than the overall dietary pattern that is beneficial.…”
Section: Nature Reviews | Nephrologymentioning
confidence: 86%
“…The trend of studies examining dietary patterns for CKD populations does note that these patterns reflect local food habits. The DIET-HD study identified "fruits and vegetables" and "Western" dietary patterns for 8,110 MHD patients across 10 European countries and Argentina 16 . These dietary patterns are also consistent with reported patterns for the general population within these same countries 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The à posteriori approach generates information on the population-specific dietary patterns, which facilitates a better understanding of health outcomes associated with locally relevant dietary patterns and development of culturally tailored nutrition intervention 13 . Appropriately, some studies have examined the association between the à posteriori derived dietary patterns and health related outcomes in MHD patients, such as nutritional risk 14 and mortality 15 , 16 . A controlled feeding study in a non-chronic kidney disease (CKD) population has also reported that dietary phosphate bioavailability assessed using urinary phosphate excretion varies by dietary patterns 17 .…”
Section: Introductionmentioning
confidence: 99%
“…As there may be variability in patients' dietary potassium intake over time, we had purposefully selected the FFQ as our dietary assessment tool given that it is representative of ''habitual'' food intake and is the preferred method for measuring nutrients with high day-to-day variability in epidemiologic studies. 21 Although the FFQ has been used in a growing number of studies of the end-stage renal disease population, 4,[32][33][34] dialysis patients may be particularly prone to more dietary fluctuations (i.e., due to more frequent dietary counseling available in outpatient dialysis centers) compared to nondialysis patients; hence, further studies examining the dietary potassium intake-mortality association using longitudinal assessments over time are needed. Second, while we were able to include serum albumin as a proxy of both nutritional status and inflammation (i.e., negative acute phase reactant), we were not able to examine other nutritional inflammatory markers and cannot exclude the possibility of residual confounding on this basis.…”
Section: Dietary Potassium In Hdmentioning
confidence: 99%